Intermittent shading can moderate coral bleaching on shallow reefs - Butcherine, Peter; Tagliafico, Alejandro; Ellis, Sophia L.; Kelaher, Brendan P.; Hendrickson, Conor; Harrison, Daniel (Frontiers in Marine Science, 2023)
The health of coral reefs is declining from the effects of human activity and climate change. Mass coral bleaching is often triggered by elevated water temperature and excessive solar irradiance. Shading can reduce coral bleaching risk. Shading-based management interventions, such as whole-of-reef marine fogging, have been proposed as a conservation tool for periods when coral undergoes excessive thermal stress. This study examined the effect of intermittent shade (30% for 0, 4, or 24 h) on two coral species, Duncanopsammia axifuga and Turbinaria reniformis, held at either 26.4°C or 32.4°C for 18 days. Coral fragments were assessed for bleaching (relative mean intensity of grey, chlorophyll a, and symbiont density), photochemistry (PAM fluorometry), and antioxidant biomarkers (SOD and CAT). Shading responses were species-specific, with T. reniformis more responsive to shading than D. axifuga. Thirty per cent shading delayed bleaching up to three-degree heat weeks (DHW), and 24 h shade was more protective than 4 h shade. Shading suppressed catalase activity in T. reniformis. Overall, our results suggest that intermittently shading corals for 4 h can moderate light stress and slow bleaching in some corals and could improve the efficiency of active solar radiation management in marine ecosystems.